Gastro-esophageal reflux disease and Barrett’s esophagus: an overview with an histologic diagnostic approach: Review - Mastracci, Luca; Grillo, Federica; Parente, Paola; Unti, Elettra; Battista, Serena; Spaggiari, Paola; Campora, Michela; Scaglione, Giulia; Fassan, Matteo; Fiocca, Roberto (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
The first part of this overview on non-neoplastic esophagus is focused on gastro-esophageal reflux disease (GERD) and Barrett’s esophagus. In the last 20 years much has changed in histological approach to biopsies of patients with gastro-esophageal reflux disease. In particular, elementary histologic lesions have been well defined and modality of evaluation and grade are detailed, their sensitivity and specificity has been evaluated and their use has been validated by several authors. Also if there is not a clinical indication to perform biopsies in patient with GERD, the diagnosis of microscopic esophagitis, when biopsies are provided, can be performed by following simple rules for evaluation which allow pathologists to make the diagnosis with confidence. On the other hand, biopsies are required for the diagnosis of Barrett’s esophagus. This diagnosis is the synthesis of endoscopic picture (which has to be provided with the proper description on extent and with adequate biopsies number) and histologic pattern. The current guidelines and expert opinions for the correct management of these diagnosis are detailed.